(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The focus of this study was to empirically examine the impact of mobile technologies’ competency on utilization among 148 freshmen students in college of computer science and information technology at Hadhramout University using the frameworks of UTAUT model. The results indicated that undergraduates in CS & IT departments are highly utilized mobile technologies. It could be also figured out that they were extremely capable to use these devices. Moreover, it was revealed that undergraduates’ competency and utilization levels were so high in communication purpose due to certain social and educational reasons. Students’ competency and utilization in basic operation are strongly correlated while there is a moderate relationship between competency and utilization in communication purpose. This indicates that there is a positive relationship between the competency and utilization in basic operation and communication. Further, the results showed a strong association between independent and dependent variables while R square 78% of deviation in the dependent variable is described by the independent determinants entered in the model of multiple regression. Specifically, competency in basic operation is the highest influential variable to the utilization of mobile technologies among CS and IT undergraduates followed by competency in information seeking. Due to the results of the study, wider and greater implication of this method in college of computer science and information technology and other colleges in Hadhramout University is recommended along with the activation of the university app.